The characteristics and outcomes of patients with malignant pheochromocytoma and paraganglioma: Single-Center Experience - Gökçay Canpolat, Asena; Çorapçıoğlu, Demet (Acta Medica, 2020)
ABSTRACT Introduction: Metastatic pheochromocytomas (PCCs) and paragangliomas (PGLs) (PPGLs) are defined by the presence of metastatic disease in nonchromaffin tissue. It is rare, and there is no guidance for clinical, histological, or biochemical predictors of metastatic behavior. So, we aimed to evaluate our PPGL patients and investigate the features and treatment outcomes of our cohort. Methods: Between 2010 and 2019, 35 PCC and 3 PGL were included in the study. The age, clinical features, demographic, biochemical, radiological data, and treatment outcomes of the patients were analyzed. Results: The mean age was 38.3 ± 15.3 years, and the female to male ratio was 22/16. Twenty-one patients had hereditary causes of PCC (Multiple endocrine neoplasia (MEN) type 2A n:17; MEN2B n:4 and Neurofibromatosis n:1). The metastatic disease was seen in four of PCCs and one of PGLs. The metastatic cases were sporadic both in PCC and PGL patients. The mean greatest dimension of the primary tumor of metastatic PPGL cases was 4.5±3.2 cm. The sites for metastasis for PCC were liver, bones, lungs, and lymph nodes in all cases. Surgery was performed, cytotoxic chemotherapy, and 131I-MIBG radionuclide therapy were given for all PCCs and external beam radiation for PGL. Three of the cases were stable with cytotoxic chemotherapy and 131I-MIBG, but one case declined, and after a total of four cycles of 177Lu therapy, she died. Conclusion:: In our tertiary referral center, the majority of the patients who were followed with PGGLs have hereditary/genetic etiology. It is observed that malignant PPGLs constitute 10.5 % of our patients, the same as the literature. Patients should be directed to centers where chemotherapy and theranostic treatments with a multidisciplinary approach are present in cases of metastatic disease in an individualized manner. Keywords: Pheochromocytoma, paraganglioma, metastatic disease, theranostic treatment